Impacto del comercio internacional y la gobernabilidad en la desigualdad de ingresos: un estudio regional a nivel mundial usando modelos espaciales durante 1995-2017 - Yunga Medina, Luis Fernando (2023)
Income inequality is a key factor for economic development; thus, it is necessary to detect the factors that affect it, either positively or negatively. In regions such as Latin America and the Caribbean (LAC), one person can earn up to sixteen thousand times more than another. In this context, the objective of this research was to examine the impact of international trade and governance on income inequality in the regions of the world during 1995-2017. The study included 78 countries with information available from Standardized World Income Inequality Database (SWIID, 2019) from Harvard Dataverse version 9.2, from the Institute for Democracy and Electoral Asistance (IDEA, 2020) version 5.1, and from the World Development Indicators (WID) which are published by the World Bank (WB, 2021). Statistical tools and a spatial panel econometric strategy were used. We started with the estimation of a general Generalized Least Squares (GLS) model and Granger-type test of Dumitrescu and Hurlin (2012), then spatial lag (SAR), spatial error (SEM), Spatial Autoregressive Combined (SAC) and spatial Durbin (SDM) models. The results support the Heckscher and Ohlin (1933) theory, and that highly democratic regions reduce income inequality. Moreover, a spatial dependence of income inequality is confirmed in most regions of the world, spillover effects reflected that there are spillovers to neighboring countries. The economic policy implications encompass four important aspects: i) a thorough review of the sectors in which international trade increases inequality, ii) greater diversification of foreign trade, iii) moving towards greater transparent and fair democratization, iv) greater cooperation between countries, considering territorial differences.